2017
DOI: 10.4236/ae.2017.52006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Traps Collecting Propolis by Honey Bees

Abstract: The last few years numerous publications have been published about the properties and plant origin of propolis, the glue-like resinous product collected by honeybees. Although, only one scientific experiment has been previously conducted on propolis collection techniques by honey bees, making the relative literature extremely limited in this area. The present study scopes to evaluate the effect of the trap types on the quantity of propolis collected by honeybees. For this reason, at two different locations, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The data indicated that Summer season significantly had the highest amount of bee propolis produced, followed by spring season, then winter season, meanwhile the autumn season had the lowest amount of propolis produced (Table ,4 The four propolis traps can be arranged in the following descending order of Type 2 > 1 > 3 > traditional method. This finding was supported by those by Tsagkarakis et al, (2017) who evaluated the effect of the trap types on the quantity of propolis collected by honeybees, Results show that two hand-cut screens with smaller openings (1 × 1 mm and 2 × 2 mm) collected significantly more.…”
Section: -Bee Propolis Production In Qalyubia Governoratesupporting
confidence: 69%
“…The data indicated that Summer season significantly had the highest amount of bee propolis produced, followed by spring season, then winter season, meanwhile the autumn season had the lowest amount of propolis produced (Table ,4 The four propolis traps can be arranged in the following descending order of Type 2 > 1 > 3 > traditional method. This finding was supported by those by Tsagkarakis et al, (2017) who evaluated the effect of the trap types on the quantity of propolis collected by honeybees, Results show that two hand-cut screens with smaller openings (1 × 1 mm and 2 × 2 mm) collected significantly more.…”
Section: -Bee Propolis Production In Qalyubia Governoratesupporting
confidence: 69%
“…The highest productivity of propolis was from the colonies in the large MOTIVE with a nylon mesh at 2.52 ± 0.37 g/colony/week. According to Tsakgarakis et al [24], propolis production is higher with smaller mesh pore size, which has a larger total surface area. Pore sizes of the aluminum, nylon, and polyethylene meshes were 2 × 2 mm, 1 × 1 mm, and 2 × 2 mm, respectively.…”
Section: Productivity Of Propolis Produced By T Laevicepsmentioning
confidence: 99%